PENEMUAN HUKUM OLEH HAKIM MAHKAMAH AGUNG DALAM PUTUSAN PERKARAKEWARISAN ISLAM DI INDONESIA PADA TAHUN 1995-2014 - Shobirin Shobirin (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2018)
This article discusses about jurisprudence of the High Courtconcerning the case of inheritance among Muslim society inIndonesia. There three main issues examined: (1) law finding bySupreme Court Justice concerning the case of inheritance, (2) thedecision of the Supreme Court in the case of inheritance from theperspective of Istinbath al-hukm, and (3) the degree of progressivityof the Judge’s decision toward the issue of justice in Indonesia. Thisis a library research in which data are collected from documentsand other available resources. The method of analysis is normativequalitative.